Simulation of extrasystole in bidomain ventricular model with patient specific geometry - Cocherová, Elena; Tyšler, Milan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2023)
The goal of the study was to simulate electrical activation on the heart ventricles and body surface potentials (BSP) during extrasystole using a realistic homogeneous model of cardiac ventricles and the patient torso. Electrical activation in the ventricular model was started in the known position of the initial ectopic activation confirmed by successful ablation in the left ventricle near the heart base as well as in several other sites near this position. The propagated electrical activation in the ventricular model was modeled using bidomain reaction-diffusion equations with the ionic transmembrane current density defined by the modified FitzHugh-Nagumo equations. The torso was treated as a homogeneous passive volume conductor. The whole simulation was numerically solved in the Comsol Multiphysics environment. Simulated BSP were compared with BSP measured in a real patient during extrasystole. The polarity and shape of selected simulated and measured ECG leads as well as the whole body surface potential distribution during the initial ectopic activation were in the best accordance when the stimulated region was close to the real position of the site of initial ectopic focus.
Keywords: bidomain refraction-diffusion model; realistic ventricles and torso model; extrasystole; ECG; simulation; body surface potentials